Efek Inokulasi Bakteri Micrococcus luteus Terhadap Pertumbuhan Jamur Benang dan Kandungan Isoflavon pada Proses Pengolahan Tempe (Effect Inoculation of Micrococcus luteus to Growth of Mold and Content Isoflavone at Tempe Processing) - Bintari, Siti Harnina; P, Anisa Dyah; J, Veronika Eka; R, Rivana Citra (Biosaintifika: Journal of Biology & Biology Education, 2009)
Tempe content of aglikon isoflavone which have potency to as anticancer compound. During processing of tempe, beside tempe mold (Rhizopus oligosporus) share other microbial namely bacterium. One of the bacterium residing at tempe ecosystem is Micrococcus luteus, having the character of gram positive and can conduct genistein biotransformation and daidzein become factor II compound (6,7,4-tri hydroksi isoflavone). Its problems how amount of R.oligosporus cell and M. luteus at processing of tempe associated is full scale of yielded tempe isoflavone. The study aimed to improve full scalely tempe aglikon isoflavone through inoculation of M.luteus bacteria. Used complete random designd, with M.luteus bacteria, as independent variable and variable depended is the amount of mold cell (R..oligosporus), amount of full scale M.luteus cell and total of isoflavone. Result of one way Anava indicate that inoculation of M.luteus bacteria do not degrade the amount of R.oligosporus cell with F call (53,28) > F tab (3,10) at significancy level 5%. Amount of M.luteus cell from 1,3 x 109 cell / gr [at] fermentation first becomes 3,4 x 106 cell/gr and decrease after day fermentation second becoming 1,75 x 106 cell/gr. Proportion of increasing isoflavone content at day fermentation 1-2 from 19,1 becoming 52,7 mg/100gr. Inoculation of M. luteus bacteria increased to count isoflavone aglicone and no trouble at growth of tempe mold and it relate to the increasing of is full scale of yielded tempe isoflavone.